2012
DOI: 10.1134/s0036024412050184
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpies and heat capacities of hematoporphyrin solutions in N,N-dimethylformamide and octanol-1

Abstract: Heat effects of the dissolution of hematoporphyrin tetramethyl ether are measured on a variable temperature calorimeter for the first time in N,N dimethylformamide and octanol 1 in the temperature range of 298 to 318 K. Standard enthalpies and heat capacities of dissolution of bioligand are calculated and compared to data obtained earlier for deuteroporphyrin dimethyl ether and ethyl acetate. Partial molar heat capacities of hematoporhyrin are determined at infinite dilution using data from differential scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…An upper limit value of +1.4 kcal mol –1 was assigned to H 2 OETPP based on the enthalpy of solvation of the related dodecasubstituted porphyrin H 2 T­(NO 2 )­OEP . A search of the literature revealed a number of papers describing studies of the enthalpies of solvation of porphyrins. The data that compares most closely to our work is that reported by Berezin et al The enthalpies of solvation in chloroform for H 2 OEP (+4.1 kcal mol –1 ), H 2 TPP (+2.4 kcal mol –1 ), and H 2 T­(iPr)P (+5.9 kcal mol –1 ) reported fall within the range of values obtained in our studies. In contrast, Δ H soln reported for H 2 OETPP is negative (−8.6 kcal mol –1 ), which contradicts the trends observed in our experiments.…”
Section: Results and Discussionsupporting
confidence: 82%
“…An upper limit value of +1.4 kcal mol –1 was assigned to H 2 OETPP based on the enthalpy of solvation of the related dodecasubstituted porphyrin H 2 T­(NO 2 )­OEP . A search of the literature revealed a number of papers describing studies of the enthalpies of solvation of porphyrins. The data that compares most closely to our work is that reported by Berezin et al The enthalpies of solvation in chloroform for H 2 OEP (+4.1 kcal mol –1 ), H 2 TPP (+2.4 kcal mol –1 ), and H 2 T­(iPr)P (+5.9 kcal mol –1 ) reported fall within the range of values obtained in our studies. In contrast, Δ H soln reported for H 2 OETPP is negative (−8.6 kcal mol –1 ), which contradicts the trends observed in our experiments.…”
Section: Results and Discussionsupporting
confidence: 82%
“…It allows us to avoid the mathematically incorrect differentiation procedure to compute entropic and enthalpic quantities and obtain solubility values for the temperature range studied. We have recently obtained the temperature dependence of the standard enthalpies of solution for both porphyrins and found that it can be represented by the following linear equations: 12,13…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It allows us to avoid the mathematically incorrect differentiation procedure to compute entropic and enthalpic quantities and obtain solubility values for the temperature range studied. We have recently obtained the temperature dependence of the standard enthalpies of solution for both porphyrins and found that it can be represented by the following linear equations: , normalΔ H 0 ( sol ) / kJ·mol 1 ( DDE ) = 24.68 ( 0.10 ) + 0.139 ( 0.009 ) · ( T / K 298.15 ) goodbreak0em3em⁣ s f = 0.08 kJ · mol 1 normalΔ H 0 ( sol ) / kJ·mol 1 ( HDEDE ) = 9.13 ( 0.02 ) + 0.199 ( 0.001 ) · ( T / K 298.15 ) goodbreak0em3em⁣ s normalf = 0.02 nobreak0em0.25em⁡ kJ · mol 1 where the first term is the enthalpy and the second one is the heat capacity of solution at the reference temperature, values in brackets give a standard deviation of the mean, and s f is t...…”
Section: Resultsmentioning
confidence: 99%